Light microscopy and scanning electron microscopy: A helping tool to identify the adultrant of dye from Curcuma longa L rhizome, and its ecofriendly applications on pharmaceutical products. Issue 6 (17th February 2022) - Abbas, Moneeza; Shaheen, Shabnum; Idrees, Komal; Jaffer, Mehwish; Hussain, Rana Abrar; Tabassum, Muhammad Waheed; Rasool, Ghulam
Abstract: The current study was embraced to examine the morphoanatomical distinguishing proof utilizing light microscopy (LM), scanning electron microscopy (SEM) and antibacterial activities of turmeric extract utilizing amoxicillin and ciprofloxacin. Cross over part of the rhizome is roundabout in structure. The peripheral layer is the periderm which comprises of 6–7 layers of digressively lengthened cells. This is trailed by an expansive cortex made of flimsy walled parenchyma cells with intercellular spaces. The antibacterial activities of turmeric extract in blend with drug items like amoxicillin and ciprofloxacin was likewise examined at various fixations. Different turmeric samples and drug items were gathered from various shops of Lahore. The samples were analyzed for antibacterial activities by utilizing pour plate method. In general outcomes showed fundamentally higher zone of inhibition of turmeric extract in combination with ciprofloxacin and lower zone of inhibition of turmeric extract in combination with amoxicillin. It is inferred that turmeric extract have hostile impact in blend with amoxicillin. Thus, the combination of turmeric extract with antimicrobial (amoxicillin) diminished the intensity of antibiotic. The turmeric extract have more antibacterial activity in mix with ciprofloxacin. Thus, the blend of turmeric extract with antibiotic (ciprofloxacin) expanded the intensity of antibiotic. Research highlights: Morphoanatomical study of Turmeric rhizome using light microscopy (LM) and scanning electron microscopy (SEM). The antibacterial activities of turmeric extract like amoxicillin and ciprofloxacin was also investigated at different concentrations. Abstract : Graphical representation of research work.